Tierra caliente - Plancarte, Laura; Clownfish Films Ltd; LP Films Limited (Firm) ([London?] : Clownfish Films Ltd, 2015)
Tierra Caliente is the story of an ordinary family from the state of Guerrero. His life begins to turn upside down, the imminent danger appears at the moment in which his existence is between the crossfire of drug traffickers and the military. --
Cinematographers, Eben Bolter, Richard Gillespie ; editors, Helle Le Fevre, Vera Simmonds ; music, David M Saunders.
In English and Spanish with Spanish or English subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed February 8, 2021)
Keywords: Tierra Caliente (Mexico : Region); Drug traffic -- Mexico; Drug abuse and crime -- Mexico; Drug addiction -- Mexico; Documentary films; Social problem films; Nonfiction films; Internet videos; Streaming video